Technologie du harponnage sur la côte Pacifique du Désert d'Atacama (Nord du Chili) - Ballester Riesco, Benjamín (Access archaeology., 2018)
Throughout the volume the reader will follow a representation of a marine hunter-gatherer society, a projection deriving from one of its iconic and most important material assets, the harpoon.